Auxiliar de procesos constructivos de obra en la Empresa Convias S.A.S Paipa – Boyacá (2023)
The company CONVIAS S.A.S is located in Envigado Antioquia which provides its construction, remodeling, road projects and civil works services. This work is focused on civil engineering and its importance in the construction of safe and sustainable structures. The need that was identified in this practice was the order in the collection of the data to which a management was given for its respective solution where a more orderly and understandable collection mechanism is created, which evidenced the activities carried out in the work. This need arises since the calculation reports that were handled before were a little difficult to understand and had little order in terms of data collection and activities carried out, for this need presented the solution was reached through the Mixed methodology which was the one indicated to provide an orderly and easy to understand method, through which a format was created that contained the necessary information to carry out the proposed activity, the result of this method was satisfactory in its totality since it was evidenced that by this means the data collection was generated much faster and had the order required for the specification of the activities. The objective is to contribute to the development of civil engineering, contribute to the supervision and control of the amounts of work, all this to comply with the specifications requested of this internship.